Strategi International Lesbian, Gay, Bixesual, Transgender, and Intersex Association (ILGA) dalam Mendorong Legalisasi Pernikahan Sesama Jenis di Taiwan - Majid, Annisa Amril; Burhan, Zulkhair (Journal of International and Local Studies, 2024)
The International Lesbian, Gay, Bisexual, Trans and Intersex Association (ILGA) is an international organization formed in 1978. ILGA was establisehd with the aim of voicing equal rights and calling for anti-discrimination against LGBT groups. Taiwan, in 2019 became the first country in Asia to legalize same-sex marriage. This policy cannot be separated from ILGA's influence. Through this writing, the authors review the strategy implemented by ILGA in supporting the legalization of same-sex marriage in Taiwan in 2019 using qualitative research methods and the policy influencer concept. This research describes ILGA's strategies, including; getting Taiwan government political support, how ILGA carries out political lobbying, building pro-LGBT alliances and encouraging dissemination and public knowledge regarding LGBT and same-sex marriage.